Implemention of Tri Hita Karana to increase room occupancy at Hilton Bali Resort - Dewa Ayu Indra Dewi; I Ketut Suarja; I Gusti Putu Sutarma; I Putu Krisna Arta Widana (International Journal of Green Tourism Research and Applications, 2022)
This study aimed to determine the effect of implementation of Balinese cultural value named Tri Hita Karana in increasing room occupancy at Hilton Bali Resort located in Nusa Dua, Bali. Data collection technique used were by questionnaire, interview, and document study and data analysis method were mixed (quantitative and qualitative) methods, with a concurrent mixed method strategy, especially the concurrent triangulation. The results of this study indicate that Tri Hita Karana in this hotel has a 16.6% effect on increasing room occupancy. It means Tri Hita Karana has a positive and significant effect on increasing the room occupancy.